Differences in distribution and characteristics of microplastics in sediments of the south-eastern part of the Gulf of Trieste - Jamšek, Jena; Prosen, Helena; Bajt, Oliver (Frontiers in Marine Science, 2024)
Introduction The Gulf of Trieste is prone to the accumulation of various pollutants and microplastics due to its geomorphological and hydrological characteristics. However, the distribution and sources of microplastics in this semi-enclosed area are poorly studied. The aim of our study was to determine the distribution and chemical composition of MP particles in the sediments of the Gulf of Trieste. Methods In this study, we collected 24 surface sediment samples using a Van Veen grab. Microplastics were extracted by density separation using NaCl. The size, shape, and color of the extracted microplastics were determined using an optical microscope, and the composition of the polymers was determined by Fourier transform infrared spectroscopy. Results and discussion The highest concentrations of up to 125 microplastic particles per 100 g dry sediment were found in coastal areas. Concentrations in the open sea were much lower, with an average of 3 particles per 100 g of sediment. Most of the microplastic was fibrous, made of polypropylene, 100–300 µm in size, and blue. This is the first study showing that microplastics are present in the sediments of the south-eastern part of the Gulf of Trieste. The findings suggest that microplastics exhibit a tendency to be retained within the sediment, leading to their accumulation primarily in a narrow coastal area rather than dispersing offshore. Our results will contribute to a better knowledge of the distribution and possible sources of plastics and microplastics in the Gulf of Trieste and even beyond in similar semi-enclosed marine areas.